A model for Alfvén-eigenmode-induced transport of fast ions in stellarators - C. Slaby; R. Kleiber; A. Könies; M.I. Wolf; M. Borchardt (Nuclear Fusion)
A novel model for Alfvén-eigenmode-induced transport of fast ions in stellarators is introduced. A variety of reduced transport models exists for tokamaks, but nothing comparable currently exists for stellarators. The model is built on a mixing-length approximation for relating the linear growth rates of Alfvén eigenmodes to a diffusion coefficient which enters into a nonlinear steady-state radial diffusion equation for the fast-ion density profile. Analytical theory in the local and cylindrical limits is applied for computing growth rates and frequencies of Alfvénic modes at the intersection points of continuum branches. After verifying the new reduced model against the physically more complete hybrid-gyrokinetic CKA-EUTERPE model and finding good agreement, the new transport model is applied to a Wendelstein 7-X case, where modest profile flatting can be observed. Finally, as an outlook, the tool is also applied to a device resembling a future stellarator reactor. In the reactor, due to the high alpha-particle energy, the fast-ion transport caused by the interaction with Alfvénic modes is potentially very strong. However, due to the simplifications made by the model (Landau damping is the only damping channel, no finite-Larmor-radius or finite-orbit-width effects) the transport in the reactor is likely overestimated.